Antioxidant activity of flavonoid constituents from the leaves of Macaranga tanarius - E Marliana (IOP Publishing, 2019)
Abstract. The beneficial health effect of natural flavonoids in plants is mainly because of their antioxidant properties. In the present study, antioxidant activity of isolated compounds from the leaves of Macaranga tanarius including nymphaeol C (1), solophenol D (2), nymphaeol A (3) and nymphaeol B (4) was conducted using 2,2-diphenyl-1-picrylhidrazyl (DPPH) method. The result showed that compound 2 revealed potential antioxidant activity followed by 1 and 4 with IC 50 values of 55.13, 62.14 and 72.83 µM, respectively. While compound 3 showed antioxidant activity with IC 50 value of 102.12 µM.